2009
DOI: 10.1080/02699200903026555
|View full text |Cite
|
Sign up to set email alerts
|

The development of intonation in young children with cochlear implants: a preliminary study of the influence of age at implantation and length of implant experience

Abstract: This study describes the development of emerging intonation in six children who had received a cochlear implant (CI) before the age of three years. At the time their implant was activated, the children ranged in age from 11 to 37 months. Spontaneous longitudinal speech samples were recorded from 30-minute sessions in which the child interacted with his or her mother. Data were collected 2 months before activation of each child's CI and at monthly intervals after activation for 6 months. The findings were compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 23 publications
4
18
0
3
Order By: Relevance
“…In that respect, our results are in line with the authors who found that cochlear implants have favorable effects in processing emotional content (e.g. Bat-Chava et al, 2005;Snow & Ertmer, 2009). At this time, we cannot explain why one CI child, L. K., seemed to be more successful than his two peers in mimicking the model.…”
Section: Productionsupporting
confidence: 89%
See 2 more Smart Citations
“…In that respect, our results are in line with the authors who found that cochlear implants have favorable effects in processing emotional content (e.g. Bat-Chava et al, 2005;Snow & Ertmer, 2009). At this time, we cannot explain why one CI child, L. K., seemed to be more successful than his two peers in mimicking the model.…”
Section: Productionsupporting
confidence: 89%
“…The behavior of younger children in this study, albeit more anecdotal than conclusive, speaks in favor of those who believe that both the chronological and the hearing age should be taken into consideration (e.g. Snow & Ertmer, 2009;Volkova et al, 2012). On one hand, hearing experience is crucial in developing good speech perception and production skills but, clearly, general cognitive development is an important factor as well.…”
Section: Productionmentioning
confidence: 61%
See 1 more Smart Citation
“…Since these children were initially delayed but later performed in the average range, their rate of change was accelerated compared to children with NH. In other studies, Snow and Ertmer (2009) looked at the development of intonation in preschool children with CIs, and Ertmer and Inniger (2009) looked at the development of utterance frequency and complexity in two young children with CIs. These studies with children with HAs and CIs suggest that those children with HL may have experienced more rapid acquisition of certain linguistic features than their peers with NH.…”
Section: Discussionmentioning
confidence: 99%
“…Snow and Ertmer (2009) studied the development of intonation in a longitudinal study of 6 children who received a cochlear implant between the ages of 10–36 months. Spontaneous speech samples were collected 2 months prior to implant activation and monthly for 6 months after activation.…”
Section: Introductionmentioning
confidence: 99%